(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
The influences of various information sources on undergraduate students’ knowledge of drug abuse encompass a broad spectrum of factors including familial dynamics, peer interactions, media exposure, education and community programme, and healthcare interventions. Understanding these influences is critical as they collectively shape the perceptions and awareness of drug abuse among students. Despite the diversity of these sources, empirical studies specifically exploring their impacts on undergraduate students’ understanding of drug abuse are limited. This study aims to fill this gap by examining how different information sources contribute to undergraduate students’ knowledge of drug abuse. Through qualitative methods involving semi-structured interviews with a sample of ten participants, thematic analysis was employed to elucidate the findings. The research reveals a notable preference among students to rely on Internet sources for information on drug abuse due to their accessibility and anonymity. However, the study underscores the importance of integrating diverse information sources comprehensively to provide a more nuanced understanding of drug abuse beyond what internet-based platforms offer. This approach is essential for equipping undergraduate students with the knowledge and insights necessary to make informed decisions and contribute to effective drug abuse prevention strategies.